Parental alienation syndrome (SAP) - Trejo Lugo, Nivar (2020)
Parental alienation syndrome (PAS) is a legal problem, which despite breaking the maternal-faternal-filial bond, has not been recognised in our legal system, nor in different countries around the world; in this sense, it is necessary to specify that PAS in the vast majority of cases is the product of failed marriages or cohabitation, and as the first symptoms are almost invisible or not very noticeable, treating them early or preventing their execution is the challenge that our society and legal system currently face. The aim of this essay is to raise awareness of this problem, which is already considered worldwide, although it is not considered a pathology by the DSM IV (Diagnostic and Statistical Manual of Mental Disorders) and is therefore little addressed and developed, despite the fact that if SAP is treated appropriately, those directly affected, i.e. the children, can avoid a problem of great magnitude throughout their lives, and not only with their parents, but also with their social environment.